MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI BERMAIN POHON ANGKA TIGA DIMENSI USIA 5-6 TAHUN DI TAMAN KANAK-KANAK AISYIYAH I KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR - Fromika, Frans Siska; ', Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase ability to recognize the concept of number in children through play group B tree numbers in Kindergarten Aisyiyah I Bangkinang City Regency Of Kampar. This study is the kind of research a class action or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically are children in group B which has 15 children in Aisyiyah I. Data were obtained through observation and data analysis was done by using quantitative descriptive analysis. The results showed that playing the numbers of trees can improve the ability to recognize the concept of number in children in group B children. It can be seen from the increase in the average percentage of children recognize the concept Numbers on the first cycle of 39.25% which is at criteria undeveloped (BB) and increased by 60 , 38% in the second cycle be 62.95% which are in developing criteria to expectations (BSH). So, play figures tree get improve the ability to know the concept of number of children aged 5-6 years in kindergarten Aisyiyah I Bangkinang City Regency Of Kampar